PEMANFAATAN APLIKASI WHATSAPP UNTUK MEDIA PEMBELAJARAN DALAM LINGKUNGAN UIN AR-RANIRY BANDA ACEH - Andika Prajana (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2017)
How to make use of ICT as a medium of learning is suspected to have been able to create an effective learning because it provides better and faster learning opportunities for students to loading material taught, displaying tasks to discussion between students and guidance with teachers can be done entirely outside formal teaching hours. Many applications were developed and web-based. One of the applications that are developed and become popular, now is a WhatsApp. WhatsApp is one of the mobile phone aplication and web-based social network that integrates with various applications used to communicate with other users, ranging from education, business, entertainment many developed this social networking site. The applications being developed today are expected to function from social networking sites like chatting or broadcasting messages, but more to the collaboration applications (collaboration applications) and information sharing (information sharing) more will find that the purpose of e-learning really can be exploited.